Produkcia antimikrobiálnych látok baktériami mliečneho kysnutia - Mančušková, Tatiana; Medveďová, Alžbeta; Valík, Ľubomír (Chemické listy, 2016)
The current tendency to limit the use of chemical preservatives in food and to extend the shelf lives of pro-ducts leads to increasing use of natural antimicrobials. Therefore, lactic acid bacteria and their metabolites are used in fermented products. Organic acids, carbon dioxide, ethanol, hydrogen peroxide, diacetyl, reuterin, bacteriocins and other substances produced by lactic acid bacteria exhibit good activity in inhibition of undesirable microbiota.
Keywords: Organic Chemicals; potraviny konzervované; Hydrogen Peroxide; Bacteriocins; Food Preservatives; konzervace potravin; peroxid vodíku; Food, Preserved; Food Preservation; Anti-Bacterial Agents; glyceraldehyd; fermentace; Diacetyl; potravinářské konzervační látky; diacetyl; grampozitivní bakterie; bakteriociny; Fermentation; organické látky; Lactobacillales; Glyceraldehyde; antibakteriální látky; Gram-Positive Bacteria